MODEL STRATEGI COPING ANAK USIA DINI DI PANTI ASUHAN KOTA MALANG - haryono, sarah emmanuel; akbar, mochammad ramli (Universitas Muhammadiyah Surabaya, 2016)
This study aimed to describe the model of coping strategies applied in the orphanage. This study uses a qualitative case study, and using model analysis techniques Miles & Hubberman. The research was done at King Kids orphanage at, Malang City. Based on research conducted, the model for coping strategies that are applied to early childhood at the orphanage is problem focused coping and emotional focused coping with learning coping strategies for early childhood in the orphanage is to use (1) the problem focused coping & emotional focused coping by (a ) sets strict rules on the environment orphanage, (b) verbal approach to the child repeatedly and continuously, (c) establish early childhood to be able to verbalize feelings and behavior in a discussion forum. (2) The purpose of learning coping strategies for early childhood in orphanages are (a) to be able to cope with all the stress experienced and (b) capable of taking a life outside the orphanage. Keywords: orphanage, caregiver, coping strategies